2020
DOI: 10.1016/j.scs.2019.101992
|View full text |Cite
|
Sign up to set email alerts
|

Vernacular passive design in Myanmar housing for thermal comfort

Abstract: Tropical weather is characterized by high humidity, high temperature, and intense solar insolation; therefore, traditional tropical housing is predominantly dependent on natural ventilation and passive cooling for thermal comfort. In the literature and practice, however, there is a gap of knowledge on Myanmar vernacular housing, specifically with regard to the variation in weather caused by climate change. In this paper, the authors review passive design techniques used in Myanmar vernacular houses to achieve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 15 publications
2
36
0
Order By: Relevance
“…Tropical buildings tend to have several openings to provide cross-ventilation. High vents prevent the creation of hot air pockets under the ceiling, to remove hot air inside and avoid mould (Rosenlund, 2000., Zune et al, 2020. All these tropical vernacular architecture mechanisms can be seen in vernacular Myanmar (Zune et al, 2020), Thai (Stagno, 2001., Tantasavasdi et al, 2001,…”
Section: Tropical Architecturementioning
confidence: 99%
See 3 more Smart Citations
“…Tropical buildings tend to have several openings to provide cross-ventilation. High vents prevent the creation of hot air pockets under the ceiling, to remove hot air inside and avoid mould (Rosenlund, 2000., Zune et al, 2020. All these tropical vernacular architecture mechanisms can be seen in vernacular Myanmar (Zune et al, 2020), Thai (Stagno, 2001., Tantasavasdi et al, 2001,…”
Section: Tropical Architecturementioning
confidence: 99%
“…above the ASHRAE's 80% comfortable upper limit, based on adaptive thermal comfort equation s (Toe and Kubotab, 2015). A simulation experiment for Myanmar housing found that for approximately 20% of the year indoor air temperatures are above 32ºC in timber housing located in the tropical monsoon climate zone and the equatorial winter dry climate zone (Zune et al, 2020). What can be learned from the existing literature is that although "the built form and materiality of vernacular buildings may suggest their climatic provenance, in itself, this is hardly proof of all-year environmental performance" (Weber and Yannas, 2014), and the same inference is true for thermal performance.…”
Section: Tropical Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…Among these tools, IES-VE is a popular commercial software used worldwide including China [55]. The validation and accuracy of this software have been proven by the BESTEST (Building Energy Simulation Test) standard of the International Energy Agency (IEA), green building rating schemes and amounts of existing studies [56][57][58][59]. Moreover, it has extensive capabilities for modeling customize systems and controls, which allows for the simulation of the intermittent operation mode of air conditioners in the case study.…”
Section: Calculation Of Operational Energy Consumption Of the Hypothementioning
confidence: 99%